2013
DOI: 10.1016/j.neuroscience.2013.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Chronic binge-like alcohol consumption in adolescence causes depression-like symptoms possibly mediated by the effects of BDNF on neurogenesis

Abstract: Here we investigated whether changes in neurogenesis and BDNF expression are possible mechanisms involved in the depression-like symptom during the withdrawal/abstinence period after chronic binge-pattern alcohol consumption given the limited number of studies addressing the link between these factors in the adolescent brain. Forty-seven male Sprague-Dawley rats were used in the study and the experimental protocol started when rats were 25-days old. Rats were assigned to either: (a) ethanol or (b) control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
89
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 59 publications
(81 reference statements)
8
89
3
2
Order By: Relevance
“…In our study, we found that both binge-pattern drinkers and more severe AUD patients had a higher mean BDNF level, particularly in those without MD as comorbidity. Studies that show negative associations between binge-pattern drinking and BDNF levels reason higher concordance between binge pattern drinking and depression (Briones & Woods, 2013). However, our sample did not show this relationship.…”
Section: Discussioncontrasting
confidence: 92%
“…In our study, we found that both binge-pattern drinkers and more severe AUD patients had a higher mean BDNF level, particularly in those without MD as comorbidity. Studies that show negative associations between binge-pattern drinking and BDNF levels reason higher concordance between binge pattern drinking and depression (Briones & Woods, 2013). However, our sample did not show this relationship.…”
Section: Discussioncontrasting
confidence: 92%
“…Previously, Segal and co-workers showed that TrkA glycosylation regulates the receptor subcellular localization and activity (55). Although only four N-glycosylation sites are conserved in the Trk family (Asn 26 , Asn 90 , Asn 174 , and Asn 223 ), differences in N-glycosylation may also affect the specificity of ligand-receptor interaction (50). Our observation that neuronal maturation regulates the agonistic effect of 7,8-DHF toward TrkB suggests that TrkB glycosylation might play some role in mediating this event.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, 7,8-DHF rescues synaptic plasticity in aged animals (22)(23)(24). Moreover, 7,8-DHF induces neurogenesis and dampens the development of the "depressive" phenotypes in chronic social defeat and binge-like alcohol consumption mouse models (25,26). Remarkably, 7,8-DHF imitates BDNF and regulates the consolidation of emotional learning (27)(28)(29), rescues the BDNF deficiency-induced learning and memory phenotypes in proprotein convertase PC7 knockout mice (30), and exhibits therapeutic efficacy in a mouse model of Rett syndrome (MeCP2 mutant mice that have reduced levels of BDNF) (31).…”
mentioning
confidence: 99%
“…During testing, mice had the same dietary regime, but they had the option between regular tap water and either sucrose (1 %) or saccharine (0.05 %) solutions, presented in graduated 100-mL glass bottles with a drinking well that extended 4 cm into the cage. Concentrations of sucrose and saccharin were chosen following the ones used by other authors [29][30][31][32]. Bottles were placed symmetrically on the food container, and they were switched every day to avoid position preference.…”
Section: Two-bottle Choice Testmentioning
confidence: 99%